68Ga-PSMA-11 PET/MR Can Be False Positive in Normal Prostatic Tissue. (April 2019) - Ferraro, Daniela A.; Rupp, Niels J.; Donati, Olivio F.; Messerli, Michael; Eberli, Daniel; Burger, Irene A.
Abstract : Abstract: Prostate-specific membrane antigen (PSMA) is a transmembrane glycoprotein expressed in the cytosol of normal prostate tissue and highly overexpressed on the membrane of prostate cancer, therefore increasingly used to image prostate cancer. We report a case of a 65-year-old man with two focal PSMA-positive areas on a 68 Ga-PSMA-11 PET/MR, one corresponding to a prostate carcinoma (Gleason score 4 + 3) and another region without any evidence of malignancy, but with corresponding high PSMA-expression on immunohistochemistry.